Upaya Revitalisasi Pertanian Rumput Laut Dalam Praktik Pariwisata Di Desa Lembongan, Kabupaten Klungkung - Pradnyana, I Wayan Gede Wahyu; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 7 No 2 (2019): VOL 7, NO 2 (2019): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2019)
Lembongan Village is one of the areas that is famous for producing the most seaweed in Nusa Penida Subdistrict, Klungkung Regency. The development of tourism in Nusa Lembongan has led to the increasingly marginalized seaweed farming seen from the decreasing number of farmers and agricultural land switching to the tourism sector. This research is important to be carried out in developing seaweed farming revitalization strategies in tourism practices in Lembongan Village. The research method used is a qualitative method with qualitative descriptive data analysis techniques. Data sources used are primary and secondary data. Data collection techniques are done by observation, in-depth interviews, and documentation. Determination of the informant is done by purposive sampling procedure. The results of this study indicate that strategies that can be pursued in the process of revitalizing seaweed farming include; the composition of stakeholders of seaweed farming by three actors, aspects of inhibiting factors and supporting factors of seaweed farming so as to create efforts that can be done to revitalize seaweed farming. Public awareness in the field of seaweed farming should be increased, especially concerns among young people as the next generation Keyword: Revitalization, Seaweed Agriculture, Tourism Practices